2014
DOI: 10.1016/j.eururo.2014.08.059
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Tobacco Use and Prostate Cancer Mortality and Incidence in Prospective Cohort Studies

Abstract: Context An association between tobacco smoking and prostate cancer (PCa) incidence and mortality was suggested in an earlier meta-analysis of 24 prospective studies in which dose–response associations and risks per unit of tobacco use were not examined. Objective We investigated the association between several measures of tobacco use and PCa mortality (primary outcome) and incidence (secondary outcome) including dose–response association. Evidence acquisition Relevant articles from prospective studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
140
4
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 96 publications
10
140
4
21
Order By: Relevance
“…For smokers, although only a near trend was observed as a risk for prostate cancer in this study ( P  = .109), meta‐analysis shows a significant correlation for current smoking 6. A possible reason for the meagre significance may be due to the lack of information regarding the amount of smoking per individual and perhaps a breakdown by pack‐years may show a significant risk among heavy smokers, as a dose‐response effect of smoking was observed for prostate cancer mortality 6. Tobacco smoke contains numerous compounds that can promote cancer and agents such as polycyclic aromatic hydrocarbons (PAH) have been shown to enhance cancer of the lung, bladder, and head and neck 12.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…For smokers, although only a near trend was observed as a risk for prostate cancer in this study ( P  = .109), meta‐analysis shows a significant correlation for current smoking 6. A possible reason for the meagre significance may be due to the lack of information regarding the amount of smoking per individual and perhaps a breakdown by pack‐years may show a significant risk among heavy smokers, as a dose‐response effect of smoking was observed for prostate cancer mortality 6. Tobacco smoke contains numerous compounds that can promote cancer and agents such as polycyclic aromatic hydrocarbons (PAH) have been shown to enhance cancer of the lung, bladder, and head and neck 12.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies demonstrate acetaldehyde to affect cellular properties such as DNA synthesis and repair,24 cause DNA mutations and adducts24, 25 and undergo further metabolism to form reactive radicals that can bind DNA 26. For smokers, although only a near trend was observed as a risk for prostate cancer in this study ( P  = .109), meta‐analysis shows a significant correlation for current smoking 6. A possible reason for the meagre significance may be due to the lack of information regarding the amount of smoking per individual and perhaps a breakdown by pack‐years may show a significant risk among heavy smokers, as a dose‐response effect of smoking was observed for prostate cancer mortality 6.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Cigarette smoking has been associated with higher prostate cancer mortality in all comers and more disease recurrence, metastasis, and cancer-specific mortality after surgery and radiotherapy for prostate cancer (1)(2)(3)(4)(5). Although, the pathways by which smoking affects prostate carcinogenesis and prostate cancer progression are largely unknown, several potential mechanisms have been proposed, including genetic and epigenetic changes, enhanced angiogenesis, life style factors, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The two most significant cancer risk factors, smoking and obesity, do not appear to be strong risk factors for PCa. A recent systematic review and meta-analysis summarized the current literature of tobacco use and PCa mortality and incidence (1). This meta-analysis included 51 cohort studies (50,349 incident cases and 4,082,606 cohort participants) and found a dichotomized association between smoking and PCa risk.…”
mentioning
confidence: 99%